The Δ33-35 Mutant α-Domain Containing β-Domain-Like M3S9 Cluster Exhibits the Function of α-Domain with M4S11 Cluster in Human Growth Inhibitory Factor - Qingui Bao; Zhichun Ding; Zhong-Xian Huang; Xiangshi Tan (Bioinorganic Chemistry and Applications)
Neuronal growth inhibitory factor (GIF), also known as metallothionein (metallothionein-3), impairs the survival and neurite formation of cultured neurons. It is known that the α-β domain-domain interaction of hGIF is crucial to the neuron growth inhibitory bioactivity although the exact mechanism is not clear. Herein, the β(MT3)-β(MT3) mutant and the hGIF-truncated Δ33-35 mutant were constructed, and their biochemical properties were characterized by pH titration, EDTA, and DTNB reactions. Their inhibitory activity toward neuron survival and neurite extension was also examined. We found that the Δ33-35 mutant α-domain containing β-domain-like M3S9 cluster exhibits the function of α-domain with M4S11 cluster in hGIF. These results showed that the stability and solvent accessibility of the metal-thiolate cluster in β-domain is very significant to the neuronal growth inhibitory activity of hGIF and also indicated that the particular primary structure of α-domain is pivotal to domain-domain interaction in hGIF.